Portraits : the Hasidic legacy of Elie Wiesel - Patterson, David, 1948- (Albany : State University of New York Press, 2021)
"Explores Elie Wiesel's portraits of the sages of Judaism and elaborates on the Hasidic legacy from his life and his teaching"--
A Post-Holocaust Hasidic Legacy -- The Portrait of the Who -- Portraits from the Torah -- Portraits from the Prophets -- Portraits from the Writings -- Portraits from the Talmud -- Portraits of the Hasidic Masters -- The Messiah: Portrait of an Anticipation.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on December 06, 2021).
JSTOR
Keywords: Wiesel, Elie, -- 1928-2016 -- Criticism and interpretation; Wiesel, Elie, -- 1928-2016; Hasidism; Hassidisme; Hasidism; LITERARY CRITICISM / Jewish; Hasidism; Criticism, interpretation, etc